170 OUTCOMES OF HEART TRANSPLANT RECIPIENTS USING BASILIXIMAB, A CHIMERIC ANTI-INTERLEUKIN-2 RECEPTOR MONOCLONAL ANTIBODY: THE PUERTO RICAN EXPERIENCE. (1st January 2006) - Banchs, H. L.; González, V.; González, I. F.; Quintana, C.; Calder—n, R.; Altieri, P. I.
Abstract : Background: Immunosuppressive therapy in heart transplantation is evolving. Induction immunotherapy in addition to standard triple therapy at the time of cardiac transplantation with cytolytic antibodies has been used in recipients with pretransplant renal impairment and to prevent rejection. Recently anti-interleukin-2 receptor monoclonal antibodies have being used for these purposes. A retrospective study of 58 heart transplant recipients was conducted to assess the effect of basiliximab, a chimeric anti-interleukin-2 receptor monoclonal antibody on biopsy proved acute rejection, creatinine clearance, serum creatinine, hospitalizations due to infection, and mortality 1 year after transplantation. Methods: A total of 58 patients charts were reviewed. The dose of basiliximab 20 mg infusion on day 0 and day 4 was selected. All patients received triple immunosuppressive therapy with cyclosporine or tacrolimus, mycophenolate mofetil, and prednisone at 24 hours post-transplant. Among the patients in the induction group 23 were males and 4 females with a mean age of 43.68 (16-62) years. In the group of patients without induction therapy, 20 were males and 11 females with a mean age of 49.58 (11-60) years. Both groups had similar pretransplant characteristics with a mean creatinine clearance of 73.97 (SD 30.54) mL/min and an average serum creatinine of 1.152 mg/dL (SD 0.24) in the induction group and 84 mL/min (SD25.49) and 1.023 mg/dL (SD.36) in the the group without induction respectively. Analysis of 0-3-, 4-6-, 7-12-month intervals post-transplant was performed. The incidence of acute rejection episodes, patient survival, and hospitalizations due to infection was analyzed. Results: Twenty-seven patients received induction therapy with basiliximab and 31 patients did not. At 0-3 month-, 4-6-month intervals and overall period, basiliximab reduced significantly the proportion of patients who experienced confirmed biopsy acute rejection episodes (p = .005) but not at the 7-12-month interval. There were no statistical differences in hospitalizations due to infection among groups (p = .2).There were two deaths in the basiliximab group, one due to infection and the other due to acute graft failure at 0-3 months post-transplant. There was no difference in post-transplant renal function between both groups at any interval studied. Conclusion: Induction therapy with basiliximab significantly reduced the number of acute rejection within the first year after transplantation, without a negative impact on patient's renal function, risk of infection, or mortality.